A comparative study of non-alcoholics, alcoholic abusers and alcoholic dependants on state-trait anxiety - Raj, S. John Michael (2005)
The disastrous psychological effect of alcohol consumption is a very serious problem of the present society. The present study tries to find an answer regarding the possible differences between non-alcoholics and alcoholics with regard to their health status. As the literature survey shows that two different types of alcoholics exist in the society, these two types were separately included in the study. They are alcoholic abusers and alcoholic dependants. The State-Trait Anxiety Inventory developed by Spielberger (1970) is used to access the levels of state-trait anxiety of the subjects in this study. The findings of the present study reveal that consistent and systematic differences exist between the non-alcoholics, alcoholic abusers, and alcoholic dependants with regard to their state and trait anxiety. - Reproduced.
Keywords: Alcoholism